In silico analysis of mitochondrial DNA genes: implication for conservation of Tor putitora (Hamilton, 1822) - Kushal Thakur; Deepika Sharma; Ankita Sharma; Amit Kumar Sharma; Danish Mahajan; Bhavna Brar; Hishani Kumari; Sandeep Kumar; Madhu Bala; Sunil Kumar; Rakesh Kumar (Scientific Reports)
Abstract Tor putitora is an endangered cyprinid fish constrained to cold water and is also considered an indicator of a healthy aquatic ecosystem. The present study aimed to examine the haplotypic diversity, genetic variation and population structure of T. putitora isolates using COI and Cyt b gene sequences submitted in GenBank. Bioinformatic analysis was carried out using 106 COI and 183 Cyt b gene sequences as well as 2 reference genome sequences. Analysis of COI and Cyt b gene reveals 18 and 85 haplotypes respectively. Mutation was observed at 44 different sites in COI and 173 in Cyt b gene sequences. Haplotype 4 and haplotype 37 were considered ancestral in COI and Cyt b respectively. Analysis of COI gene reveals moderate haplotype diversity (0.630) and low Nucleotide diversity (0.00662) whereas Cyt b has higher haplotype diversity (0.804) and low Nucleotide diversity (0.00582). Moreover, the neutrality test such as Tajima’s D, and Fu’s Fs showed negative values in both gene sequences, suggesting population expansion attributed to habitat destruction. So, comprehending the genetic variability within and among the T. putitora population is crucial for conserving and managing this species. Integration of genetic diversity into conservation planning can enhance the effectiveness of breeding programs and habitat restoration efforts.